2019
DOI: 10.1634/theoncologist.2019-0403
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Stone Disease in Patients with Neuroendocrine Tumors Treated with Somatostatin Analogs: A Multicenter Study

Abstract: Background Somatostatin analogs (SSAs) are the mainstay of neuroendocrine tumor (NET) treatment. Biliary stone disease is reported as a common side effect of SSAs, with a frequency ranging from 10% to 63%. Studies on SSA‐treated patients for acromegaly report an increased incidence of biliary stone disease compared with the general population, whereas data on patients with NETs are few. Guidelines are based on weak evidence, thus resulting in conflicting recommendations. The aim of the study is to evaluate bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Most reported complications are acute cholecystitis (AC), pancreatitis, jaundice, and cholangitis, with a cumulative incidence of 0.1–4% per year. Risk factors for biliary stone disease and its complications are female gender, age, pregnancy and puerperium, obesity, comorbidities (such as liver cirrhosis, Crohn's disease or hemolytic anemia) and concomitant medications (such as hormone therapy, parenteral nutrition or somatostatin analogs) [ 1 , 3 , 4 ] .…”
mentioning
confidence: 99%
“…Most reported complications are acute cholecystitis (AC), pancreatitis, jaundice, and cholangitis, with a cumulative incidence of 0.1–4% per year. Risk factors for biliary stone disease and its complications are female gender, age, pregnancy and puerperium, obesity, comorbidities (such as liver cirrhosis, Crohn's disease or hemolytic anemia) and concomitant medications (such as hormone therapy, parenteral nutrition or somatostatin analogs) [ 1 , 3 , 4 ] .…”
mentioning
confidence: 99%
“…Among these, gallstones formation is considered as the most serious one. In a recent multi-centre large study performed on 478 NEN patients receiving somatostatin analogues (octreotide in 70% of them), an incidence for developing gallstones of 27% was reported, and biliary complications (biliary colic, acute acute cholecystitis, cholangitis, biliary pancreatitis, or obstructive jaundice) occurred in 7.5% of patients (36). In that study, previous surgery for primary small-bowel NEN was a significant risk factor for developing gallstones, thus defining a specific subgroup of patients at high-risk who should monitor during therapy for this possible side effect, and supporting the recommendation to perform cholecystectomy in those NEN patients who are candidate to surgery for primary small bowel resection.…”
Section: Discussionmentioning
confidence: 99%
“…PaƟents excluded (N=50) N=34 no resecƟon of primary tumor N=16 previous cholecystectomy Fig. 1 Flow-diagram of the selection process (− 23 to 3). The re-hospitalization rate for BSD was lower PC arm (8.9% vs. 0%; P = 0.026).…”
Section: Prophylacɵc Cholecystectomy Arm N=52mentioning
confidence: 99%
“…Biliary stone disease (BSD) is common in patients treated with somatostatin analogues (SSA) for Small-intestine neuroendocrine neoplasms (Si-NENs) [1][2][3][4]. For this reason, a recent multicentric cohort study suggested the prophylactic cholecystectomy in all patients' candidates to the resection of the primary tumors.…”
Section: Introductionmentioning
confidence: 99%